Meta-analysis of the effects of silage additives on high-moisture grain silage quality and performance of dairy cows - Torres, R. N.S. [UNESP]; Ghedini, C. P.; Coelho, L. M. [UNESP]; Ezequiel, J. M.B. [UNESP]; Júnior, G.A. Almeida; Almeida, M. T.C. (Elsevier, 2021)
Our objective was to evaluate the effects of applying silage additives to high moisture grain silage (HMGS) on its quality (objective 1) and performance of dairy cows (objective 2). Additionally, this study aimed to investigate the effects of replacing dry grain (DG) with HMGS on performance of lactating dairy cows (objective 3). Silage quality (dataset composed by 8 studies with 32 treatment means), was evaluated by weighted means difference (WMD) between the control (HMGS with no silage additives) and treated-HMGS (HMGS treated with silage additives) groups. The effects of replacing DG with HMGS on performance of lactating dairy cows (dataset composed by 18 studies with 34 treatment means) was evaluated by WMD between the control group (diets with no HMGS) and HMGS group (diets with HMGS replacing DG). Treatment means were weighted by the inverse of the variance. Applying silage additives to HMGS had no effect on silage pH (P = 0.27), DM recovery (P = 0.18), ethanol (P = 0.18) and counts of yeasts (P = 0.86) and molds (P = 0.13). However, increased silage concentrations of N-NH3 (WMD = 0.49 g/kg of total nitrogen; P < .0001), acetate (WMD = 0.75g/kg of DM; P = 0.003), and propionate (WMD = 0.08g/kg of DM; P = 0.01) were reported in treated-HMGS. Inclusion of silage additives reduced DM (P = 0.01) and aerobic stability (WMD = -26.43 h; P < .0001) of HMGS. Replacing DG with HMGS in dairy cows diets reduced intakes of dry matter (WMD = -0.38 kg/d; P = 0.003) and NDF (WMD = -0.61kg/d; P <.0001). However, increased digestibility of DM (P <.0001), crude protein (P < .0001), NDF (P = 0.05) were reported in cows receiving HMGS (replacing DG). Replacing DG with HMGS did not change milk production (P = 0.34). However, concentration (P = 0.01) and yield (P = 0.01) of milk fat and concentration of milk lactose (P = 0.03) were reduced with feeding HMGS. Concerning the effects of feeding HMGS on ruminal fermentation characteristics, ruminal pH (WMD = -0.07; P < .0001), ruminal N-NH3 concentration (WMD = -1.15 mg/dL; P = 0.04) and ruminal acetate (WMD = -1.20 mol/100mol; P = 0.02) were reduced with HMGS feeding. In conclusion, applying silage additives to HMGS had no effect on silage quality and performance of lactating dairy cows. A pronounced reduction in silage aerobic stability was reported with inoculating HMGS (P < .0001). Replacing DG with HMGS increased diet digestibility. However, feed intake and concentration of milk fat was reduced when HMGS replaced DG in amounts greater than 300g HMGS/kg of DM.
Keywords: Grain ensiling; Microbial inoculants; Milk fat